If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + -126 = 6x + -7 Reorder the terms: -126 + 13x = 6x + -7 Reorder the terms: -126 + 13x = -7 + 6x Solving -126 + 13x = -7 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -126 + 13x + -6x = -7 + 6x + -6x Combine like terms: 13x + -6x = 7x -126 + 7x = -7 + 6x + -6x Combine like terms: 6x + -6x = 0 -126 + 7x = -7 + 0 -126 + 7x = -7 Add '126' to each side of the equation. -126 + 126 + 7x = -7 + 126 Combine like terms: -126 + 126 = 0 0 + 7x = -7 + 126 7x = -7 + 126 Combine like terms: -7 + 126 = 119 7x = 119 Divide each side by '7'. x = 17 Simplifying x = 17
| 28=u-13 | | s+85=4 | | 17+7x=-8(5x-8) | | (3x-5)(5x+1)=0 | | -5(7+m)+m=-(8m+2)-2 | | 32-17=5(x-2) | | x+1/2+3/4=2 | | 177-5x=40x+17 | | -55=-10+5x | | 3x+6x-4=14 | | 5t+2=5 | | 2-(s-9)=10-s+4 | | 12(x-6)=-3-9 | | 4x+21=11x-23 | | 7x*7=4x*4 | | 8n-3n=21 | | n-728=-35 | | 793=w+964 | | 4(x-1)=2(x+8) | | 9(x+6)-48= | | 5c+6=26 | | m-531=-347 | | 7u=329 | | 8y+3=51 | | (v+7)(v-8)=0 | | -3x=-1(x-6) | | 4x^2-13x+20=4x+5 | | z-344=-245 | | (y-9)(y+3)=0 | | -2(-7n+6)-2(8n+1)=-22 | | f+50=97 | | 3(6-2x)=8x |